2021
DOI: 10.1097/hjh.0000000000002733
|View full text |Cite
|
Sign up to set email alerts
|

Beat-to-beat blood pressure variability: an early predictor of disease and cardiovascular risk

Abstract: Blood pressure (BP) varies on the long, short and very-short term. Owing to the hidden physiological and pathological information present in BP time-series, increasing interest has been given to the study of continuous, beat-to-beat BP variability (BPV) using invasive and noninvasive methods. Different linear and nonlinear parameters of variability are employed in the characterization of BP signals in health and disease. Although linear parameters of beat-to-beat BPV are mainly measures of dispersion, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 94 publications
(149 reference statements)
2
19
0
Order By: Relevance
“… 47 , 48 The measurement of BP variability could provide additional insight into the differences in hemodynamic and autonomic control between men and women. 49 , 50 However, the present methods are not well suited to the study of BP variability, as only 1 supine and 2 seated and 2 standing BP values were recorded, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 92%
“… 47 , 48 The measurement of BP variability could provide additional insight into the differences in hemodynamic and autonomic control between men and women. 49 , 50 However, the present methods are not well suited to the study of BP variability, as only 1 supine and 2 seated and 2 standing BP values were recorded, which is a limitation of our study.…”
Section: Discussionmentioning
confidence: 92%
“…Table 3 was primarily used to examine the variability of the continuous blood pressure signal. It has been demonstrated that two people with similar blood pressure can have different blood pressure volatility, and that continuously monitoring blood pressure to obtain blood pressure variability sequences can be used as a hidden indicator independent of other cardiovascular risk factors 22,40 . The standard deviation, coe cient of variation, and continuous variation of continuous blood pressure in experimental and control rats did not show signi cant differences in this study, but non-linear algorithms like sample entropy and detrended uctuation analysis were used to sensitively identify changes in blood pressure uctuations in the two groups of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The autonomic nervous system and stress re exes can be evaluated by converting recorded blood pressure and ECG data into HRV and BPV. The use of variable parameters allows for a quantitative assessment of the cardiovascular autonomic nervous system's functioning 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, aberrant beat-to-beat BPV is associated with end-organ damage related to excursions in perfusion (Wei et al, 2014). Alternatively, nonlinear parameters quantify complexity and regularity that decreases and increases in disease states, respectively (Bakkar et al, 2021). Despite the value of linear parameters of variability, fluctuations of the cardiovascular system are described as nonhomogeneous, that is, different parts of the signal exhibit distinctive scaling properties, and are thus believed to be better quantified using nonlinear parameters (Ivanov et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the value of linear parameters of variability, fluctuations of the cardiovascular system are described as nonhomogeneous, that is, different parts of the signal exhibit distinctive scaling properties, and are thus believed to be better quantified using nonlinear parameters (Ivanov et al, 2001). Indeed, entropy and detrended fluctuation analysis of the beat-to-beat BP time series are shown to possess superior power of discriminating among patient groups compared to conventional parameters of variability and average BP (Bakkar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%